First Corinthians - Montague, George T. (Catholic commentary on sacred scripture, 2011)
Cliques and the cross (1 Cor. 1) -- The power and the wisdom (1 Cor. 2) -- Our true boast is in God, not ministers (1 Cor. 3) -- Servants and stewards (1 Cor. 4) -- Cleansing the community (1 Cor. 5) -- The court and the courtesan (1 Cor. 6) -- Marriage and virginity (1 Cor. 7) -- Idols: freedom and conscience (1 Cor. 8) -- Paul's personal example (1 Cor. 9) -- Warnings and the Eucharist (1 Cor. 10) -- Problems in the community at worship (1 Cor. 11) -- Many gifts, one body (1 Cor. 12) -- Love, the heart of the gifts (1 Cor. 13) -- The gifts in practice (1 Cor. 14) -- The Resurrection (1 Cor. 15) -- Conclusion (1 Cor. 16).